1263. In Vitro Activity of Ceftazidime-avibactam and Comparator Agents against Enterobacterales and Pseudomonas aeruginosa Collected from Patients with Bloodstream Infections as Part of the ATLAS Global Surveillance Program, 2017-2019. (4th December 2021) - Lob, Sibylle; Hackel, Meredith; Stone, Gregory; Sahm, Daniel F
Abstract: Background: Avibactam (AVI) is a β-lactamase inhibitor with potent inhibitory activity against Class A, Class C, and some Class D serine β-lactamases. The combination of ceftazidime (CAZ) with AVI has been approved in Europe and in the United States for several indications. This study evaluated the in vitro activity of CAZ-AVI and comparators against Enterobacterales ( Eba ) and Pseudomonas aeruginosa ( Pae ) isolates collected from patients with bloodstream infections as part of the ATLAS surveillance program in 2017-2019. Methods: A total of 48193 Eba and 15376 Pae non-duplicate clinically significant isolates, including 9224 Eba and 1808 Pae isolated from bloodstream infections, were collected in 53 countries in Europe, Latin America, Asia/Pacific (excluding mainland China), and the Middle East/Africa region. Susceptibility testing was performed by CLSI broth microdilution. CAZ-AVI was tested at a fixed concentration of 4 µg/ml AVI. Meropenem-nonsusceptible (MEM-NS) Eba and Pae isolates were screened for the presence of β-lactamase genes. Results: Susceptibility data are shown in the Table. Percentages of susceptibility (% S) to the tested agents were 0.4-3.4% lower among Eba and Pae from bloodstream infections compared to isolates from combined sources in most cases. CAZ-AVI showed potent in vitro activity against all Eba bloodstream isolates and the CAZ-NS subset (MIC90, 0.5-4 µg/ml, 91.7-97.4% S). Reduced activity against MEM-NS Eba was attributable to carriage of class B metallo-β-lactamases (MBLs) as 98.1% of MEM-NS MBL-negative isolates were susceptible to CAZ-AVI. None of the tested comparators exceeded the activity of CAZ-AVI. CAZ-AVI also showed good in vitro activity against the majority of Pae bloodstream isolates (MIC90, 16 µg/ml, 89.7% S). Activity was reduced against CAZ-NS and MEM-NS subsets (55.9-63.0% S), which included isolates carrying MBLs, but exceeded the activity of CAZ against MEM-NS and MEM against CAZ-NS by 26-28 percentage points. Amikacin was the only tested comparator that demonstrated comparable activity against Pae bloodstream isolates. Results Table Conclusion: CAZ-AVI provides a valuable therapeutic option for treating bloodstream infections caused by MBL-negative Eba and Pae isolates. Disclosures: Sibylle Lob, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor) Meredith Hackel, PhD MPH, IHMA (Employee)Pfizer, Inc. (Independent Contractor) Gregory Stone, PhD, AztraZeneca (Shareholder, Former Employee)Pfizer, Inc. (Employee) Daniel F. Sahm, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor)